2012
DOI: 10.1371/journal.pone.0050834
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Surveillance of Low Pathogenic Avian Influenza Viruses in Wild Birds across the United States: Inferences from the Hemagglutinin Gene

Abstract: A United States interagency avian influenza surveillance plan was initiated in 2006 for early detection of highly pathogenic avian influenza viruses (HPAIV) in wild birds. The plan included a variety of wild bird sampling strategies including the testing of fecal samples from aquatic areas throughout the United States from April 2006 through December 2007. Although HPAIV was not detected through this surveillance effort we were able to obtain 759 fecal samples that were positive for low pathogenic avian influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 52 publications
(68 reference statements)
0
31
0
Order By: Relevance
“…The reintroduction of the H2 subtype into the human population would pose a significant global health threat in a population where the majority of humans now lack anti-H2 hemagglutinin (HA) serologic immunity (Pyhala 1985; Webster 1997; Nabel et al, 2011). Avian influenza virus surveillance provides evidence for the continuing circulation of H2 viruses in wild migratory birds and poultry in live bird markets (Schafer et al, 1993; Piaggio et al, 2012; Chen et al, 2010). In some cases, contemporary H2 viruses have been found to be antigenically related to the early pandemic human viruses (Schafer et al, 1993; Piaggio et al, 2012; Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reintroduction of the H2 subtype into the human population would pose a significant global health threat in a population where the majority of humans now lack anti-H2 hemagglutinin (HA) serologic immunity (Pyhala 1985; Webster 1997; Nabel et al, 2011). Avian influenza virus surveillance provides evidence for the continuing circulation of H2 viruses in wild migratory birds and poultry in live bird markets (Schafer et al, 1993; Piaggio et al, 2012; Chen et al, 2010). In some cases, contemporary H2 viruses have been found to be antigenically related to the early pandemic human viruses (Schafer et al, 1993; Piaggio et al, 2012; Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wild aquatic birds serve as carriers and transmitters of AIV, expanding the geographic distribution of influenza viruses. In the United States, the active surveillance for AIV in wild aquatic birds initiated in 2006 has revealed that hemagglutinin (HA) gene sequences representing the H4, H8, H10, H11, and H12 subtypes are well established in North America, with no evidence of intercontinental exchange (4). Intercontinental exchange of AIV between the North American and Eurasian lineages has occurred, however, for other subtypes of lowly pathogenic AIV (H1, H2, H3, H6, H9, H13, and H16) over the past few decades (4).…”
mentioning
confidence: 99%
“…These were the only animals that were intentionally infected during this study. An H6N2 AIV was chosen as inoculum because this subtype has been associated with LBM infections in the U.S. during previous years [5], H6 viruses are prevalent in LBMs in Asia [9], and H6 AIVs are commonly found in the wild bird fauna in the U.S. [10]. The experimental design allowed the assessment of virus transmission occurring downward among cage rows (i.e., top to bottom) and horizontally to adjacent cages.…”
Section: Experimental Infectionmentioning
confidence: 99%